Echocardiographic evidence of innate aortopathy in the human intracranial aneurysm. - Yong-Won Shin; Keun-Hwa Jung; Jeong-Min Kim; Young Dae Cho; Soon-Tae Lee; Kon Chu; Manho Kim; Sang Kun Lee; Moon Hee Han; Jae-Kyu Roh (PLoS ONE, 2014)
BACKGROUND: Intracranial aneurysm (IA) is significantly more prevalent in patients with coarctation of the aorta or bicuspid aortic valve than in the general population, suggesting a common pathophysiology connecting IA and aortopathy. Here, we analyzed echocardiographic aortic root dimension (ARD) in patients with IA to confirm this possibility. METHODS: From January 2008 to December 2010, 260 consecutive patients with IA who were admitted to our institution for coil embolization or for acute stroke management and who also underwent echocardiography were enrolled. We hypothesized that patients with large, ruptured, or multiple IAs are more likely to harbor co-prevalent aortopathy as measured by ARD compared to patients with small, isolated, unruptured IAs. Eccentric group was defined as patients aged <55 years with at least one ruptured aneurysm, an aneurysm ≥7 mm in size, or multiple aneurysms; the remainder was classified into a non-eccentric group. Clinical, angiographic, and echocardiographic findings of the two groups were compared. RESULTS: ARD was significantly larger in the eccentric group than in the non-eccentric group (P = 0.049), and the difference was confirmed by multivariable analysis (P = 0.02). Subgroup analysis of patients aged <55 years showed similar result for ARD (P = 0.03), whereas hypertension was more associated with the non-eccentric group (P = 0.01). In addition, height was inversely related to aneurysm size after adjustment for age, sex, weight, ARD, smoking status, and number of aneurysms (P = 0.004). CONCLUSIONS: A certain group of IA patients share a common intrinsic wall defect with aortopathy. Shared neural crest cell origin may give rise to this phenomenon.